Nutritional Status of Participants in The Integrated Development Post for Non-Communicable Diseases : a Descriptive Study - Abdullah Azam Mustajab; Fibrinika Tuta Setiani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The study was to describe the nutritional status of participants in the Integrated Development Post for Non-Communicable Diseases. The method used was descriptive quantitative with 35 respondents. Respondents were measured anthropometrically including weight, height, waist circumference and body mass index (BMI) then descriptive analysis was carried out using SPSS. The results showed that respondents who had BMI in the obesity category were 15 (42.90%), normal 14 (40%) and obese 6 (17.10%) and based on the measurement of waist circumference, respondents who experienced central obesity were 30 (85.70%) and not central obesity were 5 (14.30%). Conclusion: Maintaining nutritional status is very beneficial because someone who is overweight is at risk of experiencing several diseases such as hypertension, diabetes mellitus and heart disease.